2007
DOI: 10.1089/neu.2007.0322
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Dysfunction in Patients with Severe Traumatic Brain Injury

Abstract: Coagulopathy is a common phenomenon in traumatic brain injury (TBI) and a major contributor to a poor outcome. Thrombocytopenia is a strong negative prognostic factor in TBI, but bleeding tendency can be present even with a normal platelet count. We investigated platelet function in patients with TBI by means of modified thromboelastography (i.e., platelet mapping [TEG-PM]). Four groups were studied: (1) patients with severe isolated TBI (n = 20), (2) patients with general trauma without TBI (the ICU group, n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
113
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(121 citation statements)
references
References 15 publications
5
113
0
3
Order By: Relevance
“…Previous authors have also reported that platelet dysfunction in TBI patients correlates with poor outcomes, [12,37] but to our knowledge, no other publications correlate TBI coagulopathy with mA or alpha-angle TEG values. Kunio et al analyzed 69 polytrauma patients with TBI and found that these patients had an increased R-time on traditional TEG [8].…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Previous authors have also reported that platelet dysfunction in TBI patients correlates with poor outcomes, [12,37] but to our knowledge, no other publications correlate TBI coagulopathy with mA or alpha-angle TEG values. Kunio et al analyzed 69 polytrauma patients with TBI and found that these patients had an increased R-time on traditional TEG [8].…”
Section: Discussionmentioning
confidence: 76%
“…Abnormalities in admission PT, aPTT, INR, and fibrinogen degradation products have all been linked to increased morbidity and mortality in TBI patients [3,4,7,12,27,28,[32][33][34][35][36][37]. However, when we analyzed admission CCT values on 1924 of our highest-level trauma activations over 18 months, no statistically significant difference in the prevalence of coagulopathy based on these values was detected in TBI patients compared to non-TBI patients (Table 2).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Brain tissue is rich in thromboplastin, and activation of clotting pathways following traumatic brain injury is thought to occur leading to abnormal coagulation. 1 Many studies have suggested possible adverse effects of disseminated intravascular coagulation and other coagulopathies on outcome of the patients. [2][3][4][5][6][7] Post-traumatic coagulopathy, in particular, appears to be linked to secondary cerebral injury.…”
Section: Introductionmentioning
confidence: 99%